Pengaruh Pelatihan dan Disiplin Kerja Terhadap Kinerja Karyawan : Literature Review Manajemen Sumber Daya manusia - Akbar Dwiansyah; Dewi Sri Woelandari Pantjolo Giningroem; Suci Indah Lestari; Widya Meliawati (PPIMAN Pusat Publikasi Ilmu Manajemen, 2024)
This research summarizes findings from related journal literature to investigate the influence of training and work discipline on employee performance. Through a literature review, this article outlines the positive relationship between work discipline and employee performance, as well as the role of work discipline in increasing efficiency and effectiveness in the workplace. The various empirical studies reviewed show that a high level of training and a strong level of work discipline can form more productive and high-performing employees. The literature also highlights the importance of integrating human resource management strategies that focus on increasing training and implementing effective work discipline. This research provides an in-depth understanding of these concepts and emphasizes their relevance in the modern organizational context. In conclusion, this article provides a solid theoretical foundation for further research and provides practical insights for human resource management in improving employee performance.